2006
DOI: 10.1007/s11099-006-0079-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abscisic acid or benzyladenine on pigment contents, chlorophyll fluorescence, and chloroplast ultrastructure during water stress and after rehydration

Abstract: With the aim to contribute to the elucidation of the role of phytohormones in response of plants to adverse environmental conditions, seedlings of Phaseolus vulgaris, Nicotiana tabacum, Beta vulgaris, and Zea mays were supplied with water, 100 μM abscisic acid (ABA), or 10 μM N 6 -benzyladenine (BA) immediately before imposition of water stress (WS). In all four species, contents of chlorophylls (Chls) and carotenoids were markedly decreased during WS and after rehydration only in plants pre-treated with water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 51 publications
4
34
1
Order By: Relevance
“…Thus both transgenics with elevated endogenous CKs coped with water stress more efficiently than WT plants (at least in case of the water loss lower than 20 %). This was in agreement with the protection of photosynthetic pigments by application of benzyladenine (BA) found in previous experiments (Haisel et al 2006). Application of BA reduced the decrease in Chl also in water-stressed wheat (Chernyad′ev and Monakhova 2003) or in Cassia (Singh et al 2001).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus both transgenics with elevated endogenous CKs coped with water stress more efficiently than WT plants (at least in case of the water loss lower than 20 %). This was in agreement with the protection of photosynthetic pigments by application of benzyladenine (BA) found in previous experiments (Haisel et al 2006). Application of BA reduced the decrease in Chl also in water-stressed wheat (Chernyad′ev and Monakhova 2003) or in Cassia (Singh et al 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Non-stomatal effects of CKs have been also reported (for recent review see Nyitrai 2005) including alleviation of the negative effects of water stress on chlorophyll (Chl) and carotenoid (Car) contents, photochemical activities of photosystem (PS) 1 and 2, and content and activity of ribulose-1,5-bisphosphate carboxylase or phosphoenol-pyruvate carboxylase (Metwally et al 1997, Chernyad′ev and Monakhova 1998, Pandey et al 2000/4, Singh et al 2001. Similarly, BA pre-treatments ceased a degradation of Chl and Car induced by water stress, increased contents of xanthophyll cycle pigments and decreased degree of their de-epoxidation (Haisel et al 2006). …”
Section: Introductionmentioning
confidence: 99%
“…3). Similar reports on chloroplast structure have also been made earlier with the application of BA under water stress in bean and sugarbeat (Haisel et al, 2006). RWC reduced under water deficit stress (Fig.…”
Section: And Ennajeh Etsupporting
confidence: 88%
“…Dias et al (2014) reported that foliar application of ABA promoted net CO 2 assimilation rate, plant dry mater accumulation and antioxidant enzyme activity. Several studies also demonstrated that ABA pre-treatment ameliorated negative effect of water stress in naturally grown barley, bean, maize, sugar beet and tobacco (Agarwal et al 2005;Haisel et al 2006;Mizrahi et al 1974). …”
Section: Resultsmentioning
confidence: 98%